Pendampingan Psikologis terhadap Anak Korban Human Trafficking - Isyatul Mardiyati (Raheema, 2019)
The sophisticated slavery or human trafficking is one of the trans-national crimes that is difficult to eradicate. This crime related to an exploitation of human, physically and psychologically, which is done by perpetrators without looking at the impact in the future. Furthermore, the psychology, social, and health problems, as well the damage of humanity values become the phenomenon which are triggered by human trafficking. For instance, the children trafficking cases, those problems rise and cause the trauma that is patched on their life. Besides, at the very young ages, they experience such horrible problems related to trafficking. Thus, the psychological guidance and counseling for children as victims of trafficking is really necessary. This action could be done in continuity and well-planned manner, that it could be restore their confidence after being the victims. Moreover, this companion program is performed in order to heal the trauma. Therefore, it could be a motivation for the victims to live their better life in the future.